THE ROLE OF THE FAMILY IN FORMING MORAL AND MORAL IMMUNITY AGAINST INFORMATION ATTACK IN YOUTH (Universal International Scientific Journal, 2026)
This thesis analyzes the role of the family in the formation of spiritual immunity against information attacks in young people. In the global information space, negative information flows that affect the ideological and psychological state of the younger generation are increasingly increasing. Therefore, the formation of youth's immunity against information attacks and their upbringing on the basis of spiritual values ​​​​is an urgent issue. The study highlights the importance of the family in the formation of youth ideology.
Keywords: Family, spirituality, ideological immunity, freedom of information